2012
DOI: 10.1021/jp303317p
|View full text |Cite
|
Sign up to set email alerts
|

Use of Dielectric Spectroscopy To Monitor Molecular Mobility in Glassy and Supercooled Trehalose

Abstract: Dielectric spectroscopy was used to comprehensively characterize the molecular mobility in amorphous trehalose, an extensively used bioprotective agent. Isothermal frequency sweeps were carried out at different temperatures in the glassy and supercooled liquid states of freeze-dried trehalose. Two previously reported secondary relaxations were observed at temperatures far below its glass transition temperature (T(g)). At temperatures close to T(g), removal of dc conductivity contribution revealed a relaxation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…Several different approaches have been used in order to reveal the existence of small intensity processes compared to the conductive signal, in the dielectric loss spectrum [17,18,19,20,21]. One of them, is based on the use of the alternative representation, in terms of the dielectric modulus, which can be evaluated from the permittivity as M* ( ω ) = 1/ ε* ( ω ).…”
Section: Resultsmentioning
confidence: 99%
“…Several different approaches have been used in order to reveal the existence of small intensity processes compared to the conductive signal, in the dielectric loss spectrum [17,18,19,20,21]. One of them, is based on the use of the alternative representation, in terms of the dielectric modulus, which can be evaluated from the permittivity as M* ( ω ) = 1/ ε* ( ω ).…”
Section: Resultsmentioning
confidence: 99%
“…reported for small molecules [27] but never in polymer materials with practical applications and with a unique experimental tech nique. Studies coupling BDS and thermally stimulated depolariza tion currents (TSDC) reported that the a mode evolved from a VFT dependence at higher frequencies (BDS in the rubbery state) to an Arrhenius dependence at lower frequencies (TSDC in the glassy state) [28].…”
Section: Molecular Mobility Associated With the Glass Transition In Ementioning
confidence: 99%
“…Therefore, mechanistic investigation of reduced crystallization tendency due to restricted molecular mobility of amorphous drugs in PASD is essential to assess their stability. DSC, 122 solid-state nuclear magnetic resonance (ssNMR), 123 and dielectric spectroscopy 124 are commonly used to monitor molecular mobility in glass systems.…”
Section: Reduction Of Molecular Mobility Of Amorphous Drug In Pasdmentioning
confidence: 99%